Understanding the microstructure evolution of Ni-based superalloy within two different fretting wear regimes in high temperature high pressure water. (September 2019) - Ming, Hongliang; Liu, Xingchen; Yan, Honglin; Zhang, Zhiming; Wang, Jianqiu; Gao, Lixia; Lai, Jiang; Han, En-Hou
Abstract: The microstructure evolution of the worn scar central areas formed on Ni-based Alloy 690 (Ni–30Cr–10Fe, wt%) within two different fretting wear regimes in high temperature high pressure (HTHP) water were studied in detail by high resolution characterization techniques. A very complex stratified structure was found within gross slip regime while only a relatively simple structure was found within partial slip regime. The wear mode and the evolution mechanisms of specific microstructures within the two different fretting wear regimes are clarified. Graphical abstract: Unlabelled Image